The Gorbachev Anti-Alcohol Campaign and Russia's Mortality Crisis - Bhattacharya, Jay (National Bureau of Economic Research, 2012)
Political and economic transition is often blamed for Russia's 40% surge in deaths between 1990 and 1994. Highlighting that increases in mortality occurred primarily among alcohol-related causes and among working-age men (the heaviest drinkers), this paper investigates an alternative explanation: the demise of the 1985-1988 Gorbachev Anti-Alcohol Campaign. Using archival sources to build a new oblast-year data set spanning 1978-2000, we find a variety of evidence suggesting that the campaign's end explains a large share of the mortality crisis - implying that Russia's transition to capitalism and democracy was not as lethal as commonly suggested